HISTORICITY AND MODERNITY OF LINGUISTICS: A STUDY - Kumar, Shobhit; Mishra, Alok (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The language of any community is not easily created. It has to go through many stages of its creation, only then it becomes a mirror of the society of that time by being grammatically correct, cultured and useful for literature. Centuries pass in the creation of the language of any community, only then languages ​​are born. This language, born from the external and internal efforts of man, travels through the group. This journey carries with it the cultural, social and religious splendor of the then society of man. All the languages ​​created by human communities are the heritage of our collective culture. The world of languages ​​in this world is so vast that it is not easily possible to have accurate and complete knowledge of it, but there is no answer to the curiosity of man either. He wants to know even those subjects which are beyond his control. God knows how many mysteries man has solved, how many are in the process of being solved and how many are still unsolved for the future. Intelligent man has always accepted these challenges. Knowing the history of language is no less than a challenge. Scholars are not unanimous on how it originated, but the tradition of its accurate study is called linguistics. When did the study of this linguistics begin in society? It is not easy for scholars to determine it correctly. Some linguists claim that the scientific study of language has been done from this specific time, while other linguists set new limits. It is not possible to get a standard solution to this problem easily. The presented research paper is a humble attempt to do a brief updated study of the study tradition of linguistics.